Ignition characteristics of an alternative kerosene from direct coal liquefaction and its blends with conventional RP-3 jet fuel. (1st May 2021) - Yang, Zhi-Yuan; Zeng, Ping; Wang, Bi-Yao; Jia, Wenlin; Xia, Zu-Xi; Liang, Jinhu; Wang, Quan-De
Highlights: Ignition characteristics of jet fuel from direct coal liquefaction (DCL) is investigated. The ignition of DCL jet fuel is compared to traditional RP-3 kerosene. Ignition characteristics of their 50/50 blend is studied. Surrogate model for the DCL jet fuel is proposed. Sensitivity analysis indicates very different dominant chemical kinetics for DCL and RP-3 kerosene. Abstract: Jet fuel from direct coal liquefaction (DCL) is an important alternative kerosene. The study of its ignition characteristics is not only critical for the development of combustion kinetic models, but also is valuable to evaluate its compatibility in current aeroengines. This work reports the first experimental study on autoignition characteristics of a jet fuel from DCL and its blends with conventional RP-3 jet fuel. Ignition delay times (IDTs) for DCL fuel, RP-3 and their blends are measured by using heated shock tube facility over a wide range of conditions. The studied pressure is 2 and 10 bar, the equivalence ratios are 0.5, 1.0 and 2.0, and the temperature range is from 920 K to 1700 K. The influence of temperature, pressure, and equivalence ratio on the IDTs is investigated. Surrogate models for the three fuels and detailed kinetic mechanism are developed to describe the combustion chemistry. Comparison between the predictions using the detailed kinetic models and the experimental data shows that the developed models exhibit acceptable performance versus the measured IDTs. Brute force sensitivity analyses are carried out to identify the key reactions controlling the ignition characteristics. The experimental data set and kinetic models extend our understanding of the ignition characteristics of alternative jet fuels.